Characteristics of cataract surgery patients influencing patient satisfaction scores. Issue 4 (April 2019) - Lee, Michele D.; Chen, Stephanie P.; Chen, Tiffany A.; Leibold, Collin; Li, Zhongqiu; Fisher, Caroline A.; Lin, Charles C.; Singh, Kuldev; Chang, Robert T.
Abstract : Purpose : To determine factors that influence patient satisfaction scores in individuals who have recently had cataract surgery. Setting : Byers Eye Institute, Palo Alto, California, USA. Design : Prospective case series. Methods : Selected questions from the Press Ganey survey and the National Eye Institute Visual Function Questionnaire‐25 were administered to each patient immediately after completion of a clinic visit. The correlation between patient‐specific variables and the answer to the survey question "likelihood of recommending our practice to others, " a surrogate for overall patient satisfaction, was assessed using the Student t test. A logistical regression model was used to adjust for potentially confounding variables. Results : One hundred forty‐three patients were recruited from 4 providers; 57 (39.8%) were men, and the mean age was 70.0 years ± 11.6 (SD). The main outcome was the proportion of scores less than 5, or "very good, " for the likelihood of recommending the practice to others. There was a statistically significant association between a non‐5 patient satisfaction score and self‐reported ethnicity of Asian or Pacific Islander compared with other ethnicities (odds ratio [OR], 2.3; 95% confidence interval [CI], 1.0‐5.1; P = .049); other possible correlates were not statistically significant. The relationship persisted after adjustment for potential confounding variables (OR, 2.6; 95% CI, 1.1‐6.3; P = .027). Conclusion : In postoperative cataract patients, Asian or Pacific Islander ethnicity, a factor out of the control of the provider and clinic staff, was associated with a lower overall Press Ganey patient satisfaction score compared with patients of all other ethnicities.